2015
DOI: 10.7860/jcdr/2015/15249.6515
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Y Chromosome Microdeletions in Idiopathic Azoospermia Cases in Central Indian Men

Abstract: The prevalence of Y chromosome microdeletions in azoospermic men was 12.8% in this geographical region. Klinefelter's syndrome is important cause in male infertility. So, the screening of Y microdeletions is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…In agreement with the study carried out by Saliminejad and Khorshid (), the current study estimated 4.72% rate of Y microdeletions in azoospermic and severe oligozoospermic infertile men (Saliminejad & Khorshid, ). Among recent Iranian studies on azoospermia, our results showed a lower frequency of microdeletions and also the frequency was lower in comparison with Indian reports (Ambulkar, Chuadhary, Waghmare, Tarnekar, & Pal, ; Ambulkar et al., ; Mahanta, Gogoi, Roy, Bhattacharyya, & Sharma, ; Mirfakhraie et al., ; Totonchi et al., ).…”
Section: Discussioncontrasting
confidence: 48%
“…In agreement with the study carried out by Saliminejad and Khorshid (), the current study estimated 4.72% rate of Y microdeletions in azoospermic and severe oligozoospermic infertile men (Saliminejad & Khorshid, ). Among recent Iranian studies on azoospermia, our results showed a lower frequency of microdeletions and also the frequency was lower in comparison with Indian reports (Ambulkar, Chuadhary, Waghmare, Tarnekar, & Pal, ; Ambulkar et al., ; Mahanta, Gogoi, Roy, Bhattacharyya, & Sharma, ; Mirfakhraie et al., ; Totonchi et al., ).…”
Section: Discussioncontrasting
confidence: 48%
“…BOULE is widely conserved across metazoa from sea anemones through humans, while DAZL is limited to vertebrates, and DAZ is further limited to Old World monkeys and apes ( Saxena et al, 1996 ; Xu et al, 2001 ). In humans, deletions encompassing the Y chromosome’s Azoospermia Factor C ( AZFc ) region, which contains all four copies of the DAZ gene, are among the most common known genetic causes of spermatogenic failure, accounting for 10% of cases of azoospermia (no sperm detected in semen) or severe oligozoospermia (abnormally low number of sperm detected in semen) in the absence of any physical obstruction ( Ambulkar et al, 2015 ; Fu et al, 2012 ; Girardi et al, 1997 ; Mascarenhas et al, 2016 ; Nakahori et al, 1996 ; Reijo et al, 1995 ; Simoni et al, 1997 ; Vogt et al, 1996 ). However, the mechanistic basis for the DAZ family’s role in spermatogenesis remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Skaletsky et al (2003) was reported that reduction of copy number to have an increased risk in infertility (Skaletsky et al, 2003;Sen et al, 2015). Deletion of AZFa and AZFb of Y chromosome can cause azoospermia or severe oligozoospermia (Vogt et al, 1996) and these results showed that all AZFa and AZFb microdeletions were present in only azoospermic infertile males (Mitra et al, 2008;Ambulkar et al, 2015).…”
Section: Discussionmentioning
confidence: 88%
“…Intra cytoplasmic sperm injection (ICSI) is prone for transmission of microdeletions to their offspring (Silber, 2011). Hence, STS-PCR based Y chromosome microdeletions screening will provide counselling to infertile couple effectively, regard to the birth of an infertile male offspring (Kuchukaslan et al, 2013;Ambulkar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%